(untitled) (Research, Society and Development, 2021)
This study seeks to understand the possible implications of the presence of the presential tutor in the teaching-learning processes of students, considering the poles of scope of the Pedagogy Course, between the years 2017 to 2019, within the scope of the Open University of Brazil (UAB). This research was carried out through the study developed in the Professional Master’s Program in Public Policies and Educational Management at the Federal University of Santa Maria. First, we sought to know the roles of presential tutor in the Pedagogy course.We sought to perceive, from the point of view of the research subjects, how the attributions of these tutors can influence the students’ teaching-learning processes. The investigation, of an applied nature, was anchored in a qualitative approach, interweaving the consultation with documents and empirical data to listen to the subjects directly involved with the course. Data collection involved semi-structured interviews with presentials tutors and a dialogical listening with students from two centers attended by the course. The data were analyzed based on the Discursive Textual Analysis, from which three categories emerged: Perception of the subjects about the activities developed by the presential tutor; Relations/interactions between the subjects involved in the teaching-learning processes in distance learning, and influence of the presential tutor in the teaching-learning processes. From this research scenario, the product resulted in the creation of a collaborative learning environment among the presentials tutors of the course, using the electronic tool Padlet.